BOD, COD, and TSS Predictions from DO measurement results for the Surabaya River, Indonesia - Mohammad Razif (Faculty of Civil Engeneering and Planning - ITATS, 2022)
The fluctuation of water quality of Surabaya river requires anticipation of online monitoring of major pollution parameters of BOD, COD, TSS for input in the drinking water treatment process. The sustainability of long-term river water quality is also very important for the sustainability of the operation of Water Treatment Installation. The purpose of this study is modelling water quality parameters to find empirical equations to calculate the value of BOD, COD, TSS from DO values with regression method and test the sustainability of Surabaya river water quality parameters using a control chart. This study developed an empirical relationship to estimate BOD, COD, TSS based on DO which has been validated statistically. The results showed that BOD, COD and TSS decreased with increasing DO and among them COD parameters decreased at a higher level compared to BOD or TSS for each increase in DO. Research data with control charts and boxplot methods also show similarities in Surabaya river water quality data characteristics for BOD, COD, TSS and DO between 2014 and 2015 which can still be tested again for the next few years to ensure the sustainability of raw water quality for drinking water treatment plants in the city of Surabaya and has great potential to be tested on rivers where raw water is used for drinking water sources in many cities in Indonesia.